2012
DOI: 10.26719/2012.18.6.556
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and low birth weight: a historical cohort study from Tehran

Abstract: This historical cohort study was designed to clarify the association between air pollution and low birth weight (LBW) amongst women referred to Tehran hospitals in 2007. In total, 225 eligible pregnant women who lived within 5 km of an air pollution monitoring station during their pregnancy were selected for the study. Data were collected via interview and hospital records. Exposure to each pollutant was estimated for each woman individually throughout her pregnancy and for each trimester. Exposures were model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…1 . After carefully reviewing these articles, we distinguished fourteen for the final analysis from 2004 to 2016 [18,24,2738] , of which six studies assessed PM 2.5 and LBW, twelve studies assessed PM 10 and LBW, and three studies assessed both birthweight and LBW. Table 1 (PM 2.5 -LBW) and Table 2 (PM 10 -LBW) show the major features of the studies chosen for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…1 . After carefully reviewing these articles, we distinguished fourteen for the final analysis from 2004 to 2016 [18,24,2738] , of which six studies assessed PM 2.5 and LBW, twelve studies assessed PM 10 and LBW, and three studies assessed both birthweight and LBW. Table 1 (PM 2.5 -LBW) and Table 2 (PM 10 -LBW) show the major features of the studies chosen for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Tehran, the capital city of Iran, is one of the most polluted cities in the world [3]. Despite applying some policies and regulations in Iran, existed evidence has revealed that the current level of air pollutants in Tehran is above healthy levels.…”
Section: Introductionmentioning
confidence: 99%
“…Some adverse outcomes of air pollution for pregnant women include low birth weight, preterm labor, and intrauterine growth retardation that in turn could be leaded to a range of childhood and adulthood morbidity and mortality later [6-8] imposing extra costs to the health system [9]. However, there is a strong believe that we could prevent pregnant women from being exposed to air pollution [3]. As such, the most suggested preventive strategy is to reduce exposure to air pollution by reducing time spent outdoors [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese women with GDM also related their health to the natural world (Helman, 2007), such as the polluted air, which demonstrated that these women have paid attention to the influence of environments on their health. Exposure to air pollution in pregnancy may influence placental growth and function (van den Hooven et al, 2012) and be associated with low birth weight (Araban et al, 2012) and fetal morbidity outcomes (Mainolfi, Salihu, Wilson, & Mbah, 2013). Based on these reasons, professionals should educate these women ways to avoid the negative influence of the natural environment on their health.…”
Section: Discussionmentioning
confidence: 99%